PENGARUH HASSAN ROUHANI DALAM MENENTUKAN ARAH KEBIJAKAN LUAR NEGERI IRAN - Muhammad Syarif Hidayat (HI 15 UMY 470, 2015)
*470 This article explaining about how Ha ssan Ro uhani’s influencing I ran f oreign p olic y towards the West. The foreign policy of Iran before the era of Rouhani was very controversial and anti - Western. In consequence , Iran was given several International sanction that put Iran in disadvantage. The personality of Rouhani that tend to be phlegmatic influencing Iran foreign policy from confrontative to more accomodative toward the West. The goal of this research is to understand on how the personality of Hassan Rouhani influencing the foreign policy of Iran towards the West especially in the relationship between Iran and United States of America about the Iran Nuclear problem . The research methode that used in this research is the library research methode and data analysis methode . The change of the for eign policy from confrontation and accommodative towards the West able to make the reputation of Iran become better in the international world and made the sanction to be lifted. The lifting of the sanction . All of the aforementioned development of Iran fo reign policy is closely related with the personality of Hassan Rouhani that tend to be phlegmatic. Kata Kunci – Hassan Rouhani, Foreign Policy , Iran , West